Pengaruh Kreativitas Siswa Terhadap Prestasi Belajar Materi Akuntasi Kelas XI IPS SMA Swasta Islam Muthmainah Ende - Sayful Amrin (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
This study aims to find out: (1) Creativity of students of class XI IPS Islamic Senior School Muthmainnah (2) Student achievement class XI IPS Islamic Senior School Muthmainnah (3) The influence of student creativity on student achievement subjects economic accounting material? Creativity of class XI student of IPS Private High School Muthmainnah Ende is in the high category. Indicated by the average value of student creativity (X) of 85.3. Student achievement class XI IPS Private High School Islamic Muthmainnah Ende is in the good category. This is indicated by the average value of learning achievement (Y) of 82.7. From the analysis there is a positive relationship beetwen the influence of student creativity and learning achievement. From result of calculation value = 25.516 bigger than = ± 2.048, it shows that there is influence of student creativity to learning achievement.